Karl Popper's Falsification In Implementation Management Chain Green Supply - MN Rizqi; Khomsiyah Khomsiyah (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2025)
Research This aim For analyze How draft Karl Popper's falsification can implemented in implementation management chain supply green. The method used is a literature study and content analysis. The results of the research obtained that Implementation paradigm Karl Popper's falsification in GSCM provides framework strong work​ For ensure that initiative green based on evidence empirical that can tested. Research conceptual about falsification in GSCM opens opportunity big For study empirical continued.